2012
DOI: 10.1128/jcm.00143-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, High-Throughput Detection of Rifampin Resistance and Heteroresistance in Mycobacterium tuberculosis by Use of Sloppy Molecular Beacon Melting Temperature Coding

Abstract: M ultidrug-resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium tuberculosis is increasing worldwide (9, 27, 37). Rapid methods to detect drug resistance are needed to quickly identify drug-resistant strains and to implement appropriate therapy (4,16,36). M. tuberculosis does not naturally contain plasmids, and almost all cases of clinical drug resistance are caused by single-nucleotide polymorphisms (SNPs) or small insertions/deletions in relevant genes (28). In the case of rifampin resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 35 publications
0
27
1
1
Order By: Relevance
“…Multiple PCR assays will therefore be needed, and optimization of assay conditions is extremely demanding due to complex oligonucleotide interactions in a multiplex format. In contrast, a more desirable and feasible approach to distinguish between closely related genotypes is to use asymmetric PCR in conjunction with MB probe-based melting curve analysis (14,15). During asymmetric PCR, a singlestranded amplicon is produced, allowing the probe to anneal and generate fluorescence at low temperature.…”
mentioning
confidence: 99%
“…Multiple PCR assays will therefore be needed, and optimization of assay conditions is extremely demanding due to complex oligonucleotide interactions in a multiplex format. In contrast, a more desirable and feasible approach to distinguish between closely related genotypes is to use asymmetric PCR in conjunction with MB probe-based melting curve analysis (14,15). During asymmetric PCR, a singlestranded amplicon is produced, allowing the probe to anneal and generate fluorescence at low temperature.…”
mentioning
confidence: 99%
“…This can arise during suboptimal drug treatment (acquired resistance) or due to mixed infection by strains with different susceptibilities, e.g., superinfection with a resistant strain in a patient with drugsusceptible TB (9). Chakravorty and colleagues reported that an rpoB Sanger sequencing assay required at least 50% of mutant DNA target in a background of wild-type DNA in order to be detected (10). Phenotypic DST methods commonly define a bacterial population as resistant if 1% or more of the organisms are resistant (11).…”
mentioning
confidence: 99%
“…The long probe length of the SMB probes and their mismatch tolerance capacity allowed us to design probes with programmable hybridization kinetics that could identify a wide range of mutations using a relatively small number of probes (34,42,53,54). Our analytic studies demonstrated robust and reproducible T m peaks that permitted error-free differentiation between wild-type and mutant target sequences, even at limiting concentrations of the target sequence.…”
Section: Discussionmentioning
confidence: 95%